2022
DOI: 10.1101/2022.10.12.511839
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural analysis of human papillomavirus E6 interactions with Scribble PDZ domains

Abstract: The cell polarity regulator Scribble has been shown to be a critical regulator of the establishment and development of tissue architecture, and its dysregulation promotes or suppresses tumor development in a context dependent manner. Scribble activity is subverted by numerous viruses. This includes human papillomaviruses (HPVs), who target Scribble via the E6 protein. Binding of E6 from high-risk HPV strains to Scribble via a C-terminal PDZ binding motif leads to Scribble degradation in vivo. However, the prec… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…To date, ETQL has been shown via GST-pull downs to bind to individual PDZ1, 3 and 4 domains of Scribble but not to PDZ2 [ 81 ]. However, a recent study [ 27 ] demonstrated that ETQL and ETQV binds to individual PDZ1, 2 and 3 but not PDZ4 domains using ITC, The differences in experimental methodologies and constructs may underpin the discrepancies with reported finding. Strikingly, an increase in the number of PDZ domains targeted by E6 correlates to an increase in E6 cancer-causing potential, with HPV-16 and HPV-18 PBMs featuring the most promiscuity with respect to their PDZ domain target selection [ 82 ].…”
Section: Human Papilloma Virus (Hpv) E6 Proteinmentioning
confidence: 94%
“…To date, ETQL has been shown via GST-pull downs to bind to individual PDZ1, 3 and 4 domains of Scribble but not to PDZ2 [ 81 ]. However, a recent study [ 27 ] demonstrated that ETQL and ETQV binds to individual PDZ1, 2 and 3 but not PDZ4 domains using ITC, The differences in experimental methodologies and constructs may underpin the discrepancies with reported finding. Strikingly, an increase in the number of PDZ domains targeted by E6 correlates to an increase in E6 cancer-causing potential, with HPV-16 and HPV-18 PBMs featuring the most promiscuity with respect to their PDZ domain target selection [ 82 ].…”
Section: Human Papilloma Virus (Hpv) E6 Proteinmentioning
confidence: 94%